2021
DOI: 10.1177/1356336x211031533
|View full text |Cite
|
Sign up to set email alerts
|

The (virtual) teaching of physical education in times of pandemic

Abstract: This study analyses the factors that affect the pedagogical practice and the consideration of the subject of physical education (PE) for a group of students in initial training to become teachers, with the intention of (a) discovering what feelings the COVID-19 pandemic arouses in the future teachers when having to teach physical education virtually, (b) investigating the advantages and disadvantages of the virtual teaching of PE during the pandemic, and (c) finding out how the pandemic has changed their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 64 publications
(73 reference statements)
0
39
0
9
Order By: Relevance
“…Previous published hybrid PE experiences agree with this perception, as teachers reported that the use of online tools for teaching and the added online interaction with students were time-demanding and resulted in increased out-of-class workload [ 15 , 33 , 34 ]. During the first wave of the COVID-19 pandemic, a group of students in initial training to become teachers expressed their concerns about the increased probability of suffering from teacher stress when following an online teaching methodology [ 35 ]. To avoid getting overwhelmed with online and blended learning, Killian et al [ 36 ] suggest that it is necessary to balance, in a manageable way, training, planning, synchronous class meetings, office hours and other teaching responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous published hybrid PE experiences agree with this perception, as teachers reported that the use of online tools for teaching and the added online interaction with students were time-demanding and resulted in increased out-of-class workload [ 15 , 33 , 34 ]. During the first wave of the COVID-19 pandemic, a group of students in initial training to become teachers expressed their concerns about the increased probability of suffering from teacher stress when following an online teaching methodology [ 35 ]. To avoid getting overwhelmed with online and blended learning, Killian et al [ 36 ] suggest that it is necessary to balance, in a manageable way, training, planning, synchronous class meetings, office hours and other teaching responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a strong relationship between the levels of mathematics acquired by the individual at the high school level and his/her mathematical literacy as a citizen. This is also true for public understanding of the science behind the pandemic and the steps taken to remedy the situation, especially when students are exposed to masses of fake news and conspiracy theories [33,34]. This is also appropriate for students that are involved in science projects.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the mental health of teachers who were forced to telework because of COVID-19, and to analyze the association with sociodemographic, teacher-related, and working conditions. (González-Calvo et al, 2021) 2021…”
Section: Studymentioning
confidence: 99%
“…Asynchronous learning allows teachers and students to connect before or after the online class through thread discussions and email, whereas synchronous learning allows teachers and students to interact during the session using methods such as video conferences or chat rooms. The change to online learning at such short notice (Müller et al, 2021) and the lack of training to cope with this new experience (González-Calvo et al, 2021) caused worry and anxiety among educators. Also, some teachers have felt irritated with the change without seen their capabilities to their strengthen (Mehta, 2021).…”
Section: Main Findingsmentioning
confidence: 99%